Atrial fibrillation and heart failure. (March 2015) - Leong-Sit, Peter; Tang, Anthony S.L.
<x xml:space="preserve">Abstract</x> Purpose of review Heart failure and atrial fibrillation are both common cardiac conditions that share multiple risk factors. Heart failure is a risk for atrial fibrillation and atrial fibrillation is a risk for heart failure. The need to understand the interplay between these two cardiac conditions and the effectiveness of management options becomes increasingly relevant. Recent findings Recent studies have focused on the prognostic nature of atrial fibrillation and heart failure, the questionable utility of digoxin and beta-blocker therapy when heart failure and atrial fibrillation coexist, and the efficacy of cardiac ablation and resynchronization therapy with concomitant heart failure and atrial fibrillation. Summary The predominant questions that require further attention with respect to atrial fibrillation and heart failure are whether catheter ablation and rhythm control offers benefit in a high-risk heart failure population with respect to mortality or heart failure reduction, and whether cardiac resynchronization therapy implantation truly benefits the subgroup of candidate patients with permanent atrial fibrillation. Large randomized multicentre studies are currently ongoing to address these important questions.